Multilocus phylogeny and revised classification for mountain dragons of the genus Japalura s.l. (Reptilia: Agamidae: Draconinae) from Asia. Issue 1 (11th October 2018) - Wang, Kai; Che, Jing; Lin, Simin; Deepak, V; Aniruddha, Datta-Roy; Jiang, Ke; Jin, Jieqiong; Chen, Hongman; Siler, Cameron D
Abstract: Although the genus Japalura s.l. has long been recognized as paraphyletic based on limited genetic sampling, its problematic taxonomy has not been revised, and phylogenetic relationships among the majority of congeners remain unknown. Here we utilize a densely sampled dataset of both multilocus genetic and morphological data to provide the first phylogenetic inference of relationships among Japalura s.l.species. Our results show that Japalura s.l. is paraphyletic, consisting of four major clades that are scattered across the phylogeny of the subfamily Draconinae: the first clade from the western, central and middle-eastern Trans-Himalayas, the second clade from the far eastern Trans-Himalayas, the third clade from East Asia and the last clade from Indochina. To address this widespread paraphyly of the genus and to stabilize the taxonomy within the family Draconinae, we revise the current taxonomy and split Japalura s.l. into four genera. By doing so, we recognize two existing generic names, Japalura sensu stricto and Pseudocalotes, resurrect one name available in the literature, Diploderma, and describe one new genus, Cristidorsa gen. nov. We discuss phylogenetic relationships and taxonomy within Japalura s.l. and present a diagnostic key to all recognized genera of the subfamily Draconinae.